Interventional gastroenterology in oncology - Wadhwa, Vaibhav; Patel, Nicole; Grover, Dheera; Ali, Faisal S.; Thosani, Nirav (CA: a cancer journal for clinicians, 2023)
Cancer is one of the foremost health problems worldwide and is among the leading causes of death in the United States. Gastrointestinal tract cancers account for almost one third of the cancer‐related mortality globally, making it one of the deadliest groups of cancers. Early diagnosis and prompt management are key to preventing cancer‐related morbidity and mortality. With advancements in technology and endoscopic techniques, endoscopy has become the core in diagnosis and management of gastrointestinal tract cancers. In this extensive review, the authors discuss the role endoscopy plays in early detection, diagnosis, and management of esophageal, gastric, colorectal, pancreatic, ampullary, biliary tract, and small intestinal cancers.